Faktor-faktor yang Mempengaruhi Kehamilan Remaja - Fitria Zuhriyatun; Puji Hastuti; Rusmini Rusmini; Walin Walin (Universitas Pahlawan Tuanku Tambusai, 2023)
The issue of sexuality in adolescence is a conversation that is always interesting to anyone. But sexuality in adolescents can have detrimental consequences for the teenager himself, family and society. The consequences caused by sexuality in adolescents include infectious diseases such as venereal diseases, HIV or AIDS, unwanted pregnancy. For this reason, researchers want to know more about